APLIKASI PERCAKAPAN BAHASA INGGRIS-BAHASA INDONESIA UNTUK TURIS MANCANEGARA BERBASIS ANDROID - Yustina Heny Wardhani; Kirana Anisya; Yang Agita Rindri; Sari Mubaroh (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2025)
Communication is one of the obstacles that often occurs to foreign tourists visiting Indonesia, this is caused by language differences between local people and tourists. Therefore, to overcome this problem, a conversation application is developed that is designed to make it easier for foreign tourists to communicate with local people. With the aim of utilizing Google Translate API technology in developing conversation applications that can be used by foreign tourists visiting Indonesia. The research method uses SDLC (Software Development Life Cycle) Waterfall which is carried out by approaching systematically which has a flow of analysis, design, coding, and testing. The results of the study obtained results in the form of a conversation application for foreign tourists visiting Indonesia that is more user friendly than Google Translate, by facilitating direct conversation without having to search on the application, and providing several additional features such as recommendations for tourist attractions, so that foreign tourists visiting Indonesia can enjoy the tourist attractions in Indonesia more. The results of the application trial that have been carried out show that the application has good performance and function through black box testing, and in subjective testing carried out using a questionnaire via Google Form with 5 respondents, the total score obtained was 180 out of 225, from the results obtained a percentage of 80%.